EDUCATIONAL MARKETING MANAGEMENT STRATEGY THROUGH SOCIAL MEDIA TO INCREASE THE INTEREST OF NEW STUDENTS - Najiah, Layli (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education marketing management is a series of activities that involve analysis, planning, implementation, implementation and evaluation. The aim of this research is to find out: (1) educational marketing planning at MTs ZaHa 3 Probolinggo, (2) implementation of educational marketing at MTs ZaHa 3 Probolinggo, and (3) evaluation of educational marketing at MTs ZaHa 3 Probolinggo. This research uses qualitative methods with a descriptive and analytical approach. Data was collected through observation, interviews and documentation techniques. The research subjects were the principal and deputy principal for public relations at MTs ZaHa 3 Probolinggo. Based on the research results, education marketing management in schools needs to be implemented with good management, both in planning, implementation and evaluation. Planning in schools is carried out through meetings or conferences with related parties to design programs that will be implemented in the future, including determining the time, place and targets to be achieved. Education marketing is carried out through various promotional methods, such as distributing brochures and outreach to target schools. The evaluation stage is carried out once every semester to ensure whether the marketing implementation is in accordance with the initial plan or still needs adjustments.